Student engagement in teacher education at the Kigali Institute of Education in Rwanda. - Nizeyimana, Gabriel (My University, 2013)
Qualitatively and quantitatively, this thesis investigates student engagement and success in post-secondary teacher education. The research is a case study conducted in Rwanda using the Classroom Survey of Student Engagement (CLASSE), interviews, and document analysis techniques. It aims at comparing two groups of teacher education students in terms of how different factors of student engagement affect their performance. The study provides a sound contribution in understanding how students with a professional background effectively engage and succeed in modules/courses of the teacher education programme that are shared with students without such background. The study claims that student teachers’ beliefs brought to teacher education play a vital role in determining the level of student engagement and performance in both professional and non-professional courses rather than their academic background. Findings indicate that these courses were taught and learnt in inappropriate teaching and learning environments. Despite unfavourable conditions, results also indicate that students with professional preparation prior to the post-secondary teacher education programme have positive beliefs about the career, interact with lecturers and peers more frequently, devote much time and effort on educationally purposeful activities, and participate more frequently in engaging activities than students who have just started teacher training. In addition, the study indicates that these factors of student engagement influence performance. The study also reveals that the former have developed their professional teacher identity which facilitates their social and academic integration and their intrinsic motivation to learning for the career while the latter are struggling learning for the profession in which they are not motivated and interested. Therefore, students with teacher identity perform significantly better than those who are new in teacher training even in non-professional courses in which they have fewer prerequisites.
Keywords: Student engagement; Performance; Teacher education; Bachelor of Education student; Beliefs; Teacher identity